MANAJEMEN PONDOK PESANTREN DALAM MENUMBUHKAN JIWA ENTREPRENEURSHIP SANTRI AL-ANSHOR AMBON (IAIN Ambon, 2023)
Abstract. As time goes by, boarding schools now no longer focus on their students to learn about something religious, but nowadays many pesantren teach or provide skills to their students for how to have potential and skills within themselves so that they can be useful for their lives after leaving the pesantren, because as time goes by the times are growing and going on, so pesantren provide skills to their students for how to face and live in an era that continues to develop. The skills that must be given by the boarding school to its students are how to become an entrepreneur or someone who has an entrepreneurial spirit within the students. The research method used is descriptive qualitative with data collection techniques of observation, interviews and documentation. Data analysis techniques use the data reduction stage, data presentation and conclusion drawing. The results showed that 1) Awakening and encouraging students to have an entrepreneurial spirit is done by motivating students to have an entrepreneurial spirit within themselves, 2) Making sincere efforts to build the entrepreneurial spirit is that the pesantren teaches and then guides students to make handicrafts that can produce so that students have an independent and creative spirit which can be useful for students, 3) Implementation steps in building the entrepreneurial spirit of santri are carried out with business units managed by Al-Anshor Islamic boarding school including cooperatives, vegetable plantations, goat farms and eucalyptus oil, 4) Human resources, namely the boarding school involves santri in managing business units so that santri have experience in managing business units. It can be concluded that the business units managed are used by the boarding school in helping santrishor to develop and foster the entrepreneurial spirit in students.